2015
DOI: 10.1007/s12094-015-1295-x
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy with liposome-bound TRAIL overcomes partial protection to soluble TRAIL-induced apoptosis offered by down-regulation of Bim in leukemic cells

Abstract: Tethering Apo2L/TRAIL to the surface of lipid nanoparticles greatly increases its bioactivity and could be of potential use in anti-tumor therapeutics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 36 publications
2
27
0
Order By: Relevance
“…Through its binding to its cognate agonistic receptors, namely, DR4 and DR5, TRAIL is able to induce apoptosis in malignant cells without harming healthy cells. Our findings are in line with other reports that combination of TRAIL as a recombinant protein (De Miguel et al, ; De Miguel et al, ; Kim et al, ; Lim et al, ; Kim et al, ; Kim et al, ; Guo et al, ; Guo et al, ; Guo et al, ; Muller et al, ) and a cDNA‐encoding TRAIL (Miao et al, ; Sun et al, ) with a large variety of carrier NPs improves its therapeutic potential. Preliminary in vivo results on the use of such hybrids are very encouraging, although the drug was always injected into the tumors directly (Perlstein et al, ; Miao et al, ; Riehle et al, ) and not intravenously.…”
Section: Discussionsupporting
confidence: 92%
“…Through its binding to its cognate agonistic receptors, namely, DR4 and DR5, TRAIL is able to induce apoptosis in malignant cells without harming healthy cells. Our findings are in line with other reports that combination of TRAIL as a recombinant protein (De Miguel et al, ; De Miguel et al, ; Kim et al, ; Lim et al, ; Kim et al, ; Kim et al, ; Guo et al, ; Guo et al, ; Guo et al, ; Muller et al, ) and a cDNA‐encoding TRAIL (Miao et al, ; Sun et al, ) with a large variety of carrier NPs improves its therapeutic potential. Preliminary in vivo results on the use of such hybrids are very encouraging, although the drug was always injected into the tumors directly (Perlstein et al, ; Miao et al, ; Riehle et al, ) and not intravenously.…”
Section: Discussionsupporting
confidence: 92%
“…In this line, our group previously demonstrated that human lymphocytes secrete TRAIL preferably associated with lipid vesicles called exosomes [35,36] Aiming to mimic this exosome-bound TRAIL, we generated the novel TRAIL formulation LUV-TRAIL, based on anchoring this death ligand on Large Unilamellar Vesicles (LUV) resembling these natural exosomes. LUV-TRAIL has been proved to be much more potent than soluble TRAIL both in haematological malignancies [37,38,41] and solid tumours [39,40]. Remarkably, the soluble version of TRAIL used in all those studies is virtually identical to the version used in clinical trials (Dulanermin®), which confers more significance to LUV-TRAIL improved efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…For protein expression analysis, Western blot was performed as previously described [38]. The following antibodies were used to analyse the expression of the main proteins involved in the extrinsic apoptotic pathway: anti-caspase-8 (BD Biosciences), anti-caspase-3 (Cell Signaling), anti-Bid (BD Biosciences), anti-PARP-1 (BD Biosciences), anti-Bax (BD Biosciences), and anti-Bak (BD Biosciences).…”
Section: Western Blot Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Most notably, apoptotic signaling via TRAIL-R2, one of the two agonistic TRAIL receptors, is not efficiently achieved by soluble homotrimeric rhTRAIL, as TRAIL-R2 requires binding of membrane-bound TRAIL or secondarily cross-linked rhTRAIL. 21,45,46 Since TRAIL-R2 is often highly expressed on cancer cells it forms an important target for TRAIL-based therapy. Importantly, we and others have previously shown that tumor-directed scFv:TRAIL fusion proteins effectively activate TRAIL-R2 on targeted cancer cells only.…”
Section: Discussionmentioning
confidence: 99%